2010
DOI: 10.1177/1533317510385810
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Responses to Horticultural-Based and Traditional Activities in Dementia Care Programs

Abstract: Engaging persons with dementia in meaningful activities supports well-being; however, care staff are challenged to implement age- and ability-appropriate activities in a group setting. We compared a randomly assigned treatment group, who received horticultural therapy-based (HT-based) programming to a comparison group, who engaged in traditional activities (TA) programming, on engagement and affect. Horticultural therapy-based programming was implemented twice weekly at 4 treatment sites for 6 weeks, while reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
67
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 32 publications
1
67
1
2
Order By: Relevance
“…, Rappe & Topo , Thelander et al . , Jarrott & Gigliotti ). The designs vary from comparative observational design to RCT design.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…, Rappe & Topo , Thelander et al . , Jarrott & Gigliotti ). The designs vary from comparative observational design to RCT design.…”
Section: Resultsmentioning
confidence: 96%
“…() and Gigliotti and Jarrot () reported higher levels on positive affect with horticultural activities compared with ordinary activities. Jarrott and Gigliotti () reported that there was no difference in affect between the groups; however, older participants showed significant lower interest.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations